Предмет: Алгебра,
автор: Funchan
Tg^2 альфа + сtg^2 альфа , если tg альфа + ctg альфа =3
Ответы
Автор ответа:
0
tg²a+ctg²a)=(tga+ctga)²-2=3²-2=9-2=7
----------------------------------
(tga+ctga)=tg²a+2*tga*ctga+ctg²a=tg²a+2*ctg²a
----------------------------------
(tga+ctga)=tg²a+2*tga*ctga+ctg²a=tg²a+2*ctg²a
Похожие вопросы
Предмет: Математика,
автор: sofijajefimova
Предмет: Українська мова,
автор: civah2011
Предмет: Математика,
автор: oksanka011087
Предмет: Алгебра,
автор: ХимБио2
Предмет: Литература,
автор: popova1985kseniya